Peningkatan Kinerja Guru Melalui Kegiatan Supervisi di SD Negeri 24 Toboali Tahun Pelajaran 2022/2023 (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
This study aims to determine the effect of supervision activities on improving teacher performance at SDN 24 Toboali in the 2022/2023 academic year. This research is correlation research. The subjects in this study were all teachers at SDN 24 Toboali. The object of this study is the performance of teachers at SDN 24 Toboali for the 2022/2023 academic year. Data collection techniques using observation, questionnaires, and documentation. The results showed that the administrative and academic supervision assessment activities carried out by the school principal had a positive and significant effect on improving teacher performance at SDN 24 Toboali. This is evidenced by an increase in the completeness of learning administration by 25%, in pre-research by 75%, and in cycle I it increased to 100%. The increase in the completeness of class administration was 14.63%, in pre-research it was 65% and in cycle I it increased to 79.63%. In addition, it was also followed by an increase in the assessment of academic supervision with a very suitable category, which increased by 19.15%, from the pre-research results of 50% and increased in cycle II to 69.15%. Thus, the supervision activities carried out by the school principal have succeeded in improving teacher performance at SDN 24 Toboali